2022
DOI: 10.18844/cjes.v17i1.6703
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for the development of ecological competence of the future preschool teachers

Abstract: The preschool period plays a key role in environmental education and shaping attitudes towards the environment. It is therefore important that preschool teachers are equipped to provide students with the necessary training in their early stages. This study aims to evaluate the new opportunities for the development of the ecological competencies of future preschool teachers in terms of the views of pre-service teachers. This research was conducted using a qualitative design. The participants of the research con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The findings also revealed that the independent efforts of students aimed at overcoming this contradiction are ineffective. The generally recognized shortcomings of university training are that students are overloaded with volumes of material being studied, insufficient development of independent work skills and a lack of self-realization skills (Nagima et al, 2023;Zhakupova, Kyakbaeva, Karimova, & Omarova, 2022).…”
Section: Research Contributionmentioning
confidence: 99%
“…The findings also revealed that the independent efforts of students aimed at overcoming this contradiction are ineffective. The generally recognized shortcomings of university training are that students are overloaded with volumes of material being studied, insufficient development of independent work skills and a lack of self-realization skills (Nagima et al, 2023;Zhakupova, Kyakbaeva, Karimova, & Omarova, 2022).…”
Section: Research Contributionmentioning
confidence: 99%
“…Given the great ecological and socioeconomic problems worldwide produced by hyper competitive approaches introduced by corporate organizations in recent years it is necessary to focus on commercially sustainable strategies (Pascucci et al, 2022), therefore, a great goal that is sought to be achieved in the industrial sector is the implementation of responsible business practices by entrepreneurs thus contributing to responsible economic growth (Del Brio et al, 2022), since, unsustainable and irresponsible consumption and production threaten nature and therefore the human being, for this reason, throughout the world many professionals focus on sustainability issues and adopt ecological strategies to preserve the environment (X. . Since a few years ago, developing countries are generating more and more waste in daily life (D. Want et al, 2022), for this, a way to quantitatively evaluate the sustainability of study centers is applying the ecological footprint method based on its application and consumption (Genta et al, 2022), on the other hand, the school and preschool stage play a fundamental role in environmental education and in the formation of good attitudes towards the environment (Zhakupova et al, 2022), because public awareness about the care of the environment plays an important role in the implementation of environmental strategies and policies (Gherhes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%